Declines in heart rate variability associated with short-term PM2.5 exposure were modified by blood pressure control and treatment: A multi-city panel study in China. (15th October 2021) - Xing, Xiaolong; Liu, Fangchao; Yang, Xueli; Liu, Qiong; Wang, Xinyan; Lin, Zhennan; Huang, Keyong; Cao, Jie; Li, Jianxin; Fan, Meng; Chen, Xiaotian; Zhang, Cuizhen; et al.
Abstract: Exposure to fine particulate matter (PM2.5 ) was associated with altered heart rate variability (HRV). However, whether blood pressure (BP) control and angiotensin II receptor blocker (ARB) treatment modifies the associations was seldom addressed. Therefore, we conducted a 3-phase panel study among 282 hypertensive subjects aged 35–74 years in four cities of China to address this issue. Real-time personal PM2.5 sampling and 24-h ambulatory electrocardiogram monitoring were performed repeatedly in 3 different seasons. Linear mixed-effects models were fitted overall and by control status of BP and ARB treatment to assess the associations between short-term PM2.5 exposure and HRV. The average hourly PM2.5 concentrations (Mean ± SD) ranged from 19.3 ± 18.2 μg/m 3 to 99.4 ± 76.9 μg/m 3 across study phases and cities. Generally, PM2.5 exposure was associated with decreased hourly and 24-h HRV. However, these adverse impacts were attenuated among patients with controlled BP (<140/90 mmHg). For each 10 μg/m 3 increment in moving average of previous 2 days' (MA2d) PM2.5 exposure, 24-h SDNN (standard deviation of NN intervals) and rMSSD (root mean square of successive RR interval differences) decreased by 0.89% (95% CI: 0.19%–1.59%) and 2.98% (95% CI: 1.04%–4.89%) among patients with uncontrolled BP (≥140/90 mmHg), whereas no obvious declines were observed among those with controlled BP ( P difference  = 0.007 and 0.022, respectively). Furthermore, ARB treatment alleviated or eliminated PM2.5 -associated declines in hourly and 24-h HRV among those with uncontrolled BP. For instance, 24-h SDNN decreased by 1.31% (95% CI: 0.54%–2.07%) with a 10 μg/m 3 increment in lag 2 days' PM2.5 exposure in ARB nonusers, whereas no obvious changes were observed in ARB users ( P difference  = 0.021). In conclusion, although PM2.5 exposure would decrease HRV, better BP control and ARB treatment could attenuate these adverse impacts, which provides supporting evidence for alleviating autonomic dysfunction of hypertension patients living in areas with high-level PM2.5 . Graphical abstract: Image 1 Highlights: Real-time personal PM2.5 monitoring was applied for 282 hypertensives repeatedly. Short-term PM2.5 exposure is associated with decreased HRV in hypertensives. Better BP control and ARB treatment alleviate the PM2.5 -related HRV declines. Abstract : Short-term PM2.5 exposure decreases HRV. Nevertheless, the PM2.5 -related HRV declines could be alleviated by better BP control and ARB treatment.